Randomized clinical trial of observational versus antibiotic treatment for a first episode of CT-proven uncomplicated acute diverticulitis. Issue 1 (30th September 2016) - Daniels, L; Ünlü, Ç; de Korte, N; van Dieren, S; Stockmann, H B; Vrouenraets, B C; Consten, E C; van der Hoeven, J A; Eijsbouts, Q A; Faneyte, I F; Bemelman, W A; Dijkgraaf, M G; et al.
Abstract: Background: Antibiotics are advised in most guidelines on acute diverticulitis, despite a lack of evidence to support their routine use. This trial compared the effectiveness of a strategy with or without antibiotics for a first episode of uncomplicated acute diverticulitis. Methods: Patients with CT-proven, primary, left-sided, uncomplicated, acute diverticulitis were included at 22 clinical sites in the Netherlands, and assigned randomly to an observational or antibiotic treatment strategy. The primary endpoint was time to recovery during 6 months of follow-up. Main secondary endpoints were readmission rate, complicated, ongoing and recurrent diverticulitis, sigmoid resection and mortality. Intention-to-treat and per-protocol analyses were done. Results: A total of 528 patients were included. Median time to recovery was 14 (i.q.r. 6–35) days for the observational and 12 (7–30) days for the antibiotic treatment strategy, with a hazard ratio for recovery of 0·91 (lower limit of 1-sided 95 per cent c.i. 0·78; P = 0·151). No significant differences between the observation and antibiotic treatment groups were found for secondary endpoints: complicated diverticulitis (3·8 versus 2·6 per cent respectively; P = 0·377), ongoing diverticulitis (7·3 versus 4·1 per cent; P = 0·183), recurrent diverticulitis (3·4 versus 3·0 per cent; P = 0·494), sigmoid resection (3·8 versus 2·3 per cent; P = 0·323), readmission (17·6 versus 12·0 per cent; P = 0·148), adverse events (48·5 versus 54·5 per cent; P = 0·221) and mortality (1·1 versus 0·4 per cent; P = 0·432). Hospital stay was significantly shorter in the observation group (2 versus 3 days; P = 0·006). Per-protocol analyses were concordant with the intention-to-treat analyses. Conclusion: Observational treatment without antibiotics did not prolong recovery and can be considered appropriate in patients with uncomplicated diverticulitis. Registration number: NCT01111253 (http://www.clinicaltrials.gov ). Abstract : Antibiotics not needed